Peran Media Sosial sebagai Alat Politik Citra Diri - Ikmah Wati; Darto Wahidin (Jurnal Ilmiah Multidisiplin Keilmuan Mandira Cendikia, 2024)
The rapid development of information and communication technology in this global era has become a challenge and opportunity for the Indonesian people. The birth of social media was able to have a significant influence on the lives of the Indonesian people. Social media is one of the things that cannot be separated from the lives of Indonesian people. Social media provides many benefits for society, including in the political field. Every individual needs to be aware of the role of social media in the political sector. The role of social media in the political field can be seen from the number of political actors who use social media as a political tool for self-image to increase their electability in the eyes of society. Seeing this, this research needs to be carried out to determine the role of social media, social media which is often used by political actors, and the role of social media as a political tool for self-image. The method in this research uses a qualitative approach which refers to library research by utilizing various sources of literature data. The results and conclusions in this research show that the role of social media in the political field is very large. This can be seen from the role of social media as a political tool for self-image which is often used by political actors to attract public attention.